Leakage current modeling of test structures for characterization of dark current in CMOS image sensors. - Loukianova, N.V (IEEE Transactions on electron devices)
In this paper, we present an extensive study of leakage current mechanisms in diodes to model the dark current of various pixel architectures for active pixel CMOS image sensors. Dedicated test structures made in 0.35-μm CMOS have been investigated to determine the various contributions to the leakage current. Three pixel variants with different photodiodes-n+/pwell, n+/nwell/p-substrate and p+/nwell/p-substrate-are described. We found that the main part of the total dark current comes from the depletion of the photodiode edge at the surface. Furthermore, the source of the reset transistor contributes significantly to the total leakage current of a pixel. From the investigation of reverse current-voltage (I-V) characteristics, temperature dependencies of leakage current, and device simulations we found that for a wide depletion, such as n-well/p-well, thermal Shockley-Read-Hall generation is the main leakage mechanism, while for a junction with higher dopant concentrations, such as n+/p-well or p+/n-well, tunneling and impact ionization are the dominant mechanisms.